Quesās i diya jako kategorie czynów zabronionych w klasycznym prawie karnym muzułmańskim – wstęp do analizy - Sadowa, Katarzyna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The main aim of the article is to briefly analyze classic Muslim criminal law’s regulations with regards to two types of crimes – homicide and bodily harm. Both these crimes are connected with the quesās (retaliation) and diya (compensetation) rules which are distinguished from islamic hudūd and ta’zir regulations. At first, the author characterizes shortly main features of Muslim criminal law, furtherfocuses on the quesās and diya rules by showing conditions of application of both punishments’ categories
Keywords: islam; prawo karne muzułmańskie; prawo karne; Quesās; diya